An examination to evaluate the achievements of the primary education stage - an analytical study - - makhlouf, samir; bounif, hanane (Journal of Social Sciences and Humanities, 2024)
The rapid developments witnessed by the outside world across the levels of technology, the fields of humanities, and society as a whole, as a result of the effects of globalization, have led and even imposed on the Algerian state a method of change in the education sector to keep pace with the developments taking place, so that the year 2022/2023 will witness another distinction that the education sector has known. Other amendments and improvements were introduced, including the introduction of English language instruction in primary education from the third year, onwards and the abolishment of the primary education certificate examination, starting in the year 2023, with an examination to evaluate the acquisitions of the primary education stage, so that the academic year 2023/2024 will also witness amendments and improvements to the process of this exam. Through this article titled “An examination to evaluate the achievements of the primary education stage,” we aim to read into some relevant concepts, and the conditions for methods and implementation of this assessment in achieving the desired goals in the primary education stage. Our research paper concluded that the standards for the achievements assessment exam provide a qualitative description of the appearance of competence. It is a national project that requires the combined efforts of all actors in the educational and societal fields, including specialists, professors, parents, and the media, to make it successful. This is a modern experience that needs to be added and revised to suit the learner’s abilities, and the involvement of specialists in educational sciences and sociology to enter schools to investigate the reality of the Algerian school.